Analysis of Mathematical Communication Ability in Terms of Student's Numerical Ability - Suci Indah Sari; Kurnia Rahmi Yuberta (Department of Mathematics, Universitas Negeri Padang (UNP), 2022)
Abstrac- This research is motivated by the low mathematical communication skills of students. Students have difficulty in expressing problems into mathematical notation and performing arithmetic operations and re-expressing mathematical descriptions. This is related to the students' numerical ability. Therefore, this study aims to describe students' mathematical communication skills in terms of high, medium and low numerical abilities. The type of research used is descriptive qualitative research. The subjects in this study were students of class X IPA-1 SMA N 1 Kec. Lareh Sago Halaban which consists of 6 students with 2 students each with high, medium and low numerical abilities. The instruments used in collecting data in this study include the researcher as the main instrument, and supporting instruments in the form of numerical ability tests, tests of students' mathematical communication skills and interview guidelines, with data collection techniques carried out by tests and interviews. The data analysis technique used is the Miles and Huberman concept, namely data reduction, data presentation and conclusion drawing. Checking the validity of the data used is triangulation technique. The results showed that subjects with high numerical abilities were easier to interpret and communicate mathematical ideas and ideas. Subjects with moderate numerical ability tend to be less capable and have little difficulty in interpreting and communicating mathematical ideas. And subjects with low numerical ability tend to be unable to interpret and communicate mathematical ideas.